(untitled) (UNED Research Journal, 2026)
Introduction: Crottin-type cheese is traditionally made with goat’s milk, which gives it a distinctive sensory profile but may be too intense for some markets and more costly to produce; partial substitution with cow’s milk may support product diversification, sensory modulation, and cost reduction. Objective: We evaluated the effect of replacing goat’s milk with cow’s milk at 0%, 50%, and 100% on yield, physicochemical characteristics, texture, color, and sensory acceptance during storage. Methods: We determined yield after manufacture. On day three, we evaluated fat, protein, salt, and overall sensory acceptance; on days three and 22, we measured moisture, % ATECAL, pH, color, and texture. We assessed consumer acceptance with 124 participants and analyzed the results by cluster analysis. Results: Protein content was the only compositional variable that differed significantly among cheeses (p<0.05), increasing with the proportion of goat’s milk. During storage, pH and moisture decreased, while % ATECAL tended to decline as cow’s milk increased. Cheese type significantly affected all color and texture variables (p<0.05), with cheese type × time interaction only for b* and C*. Hardness was greater in 100% goat’s milk cheese and increased during storage. Cluster analysis showed that 56% of consumers accepted all formulations, especially those with 0% and 50% cow’s milk; 19% rejected all formulations; and 25% preferred the 100% cow’s milk cheese. Conclusion: Replacing goat’s milk with cow’s milk modified the physicochemical, color, and textural properties of Crottin-type cheese. Sensory acceptance varied by consumer segment, indicating diversification potential rather than a single optimal formulation.